Research of material dispersion in optical materials for optical waveguides - Abdul Nasir, Abd Ghafar (2013)
Recently, the technology of optical waveguide systems has developed rapidly over the past new years. This progressive research and development have received much attention, due to its potential of offering new capabilities in application such as communication fields, optical sources and detectors and integrated optical circuits. Thus, considering optical materials as one of the major elements in optical waveguide, a study of material dispersion occurred in optical materials and its characteristics must be done seriously. Therefore, in this paper, a relation between Abbe number v and d-line refractive index nd for optical materials in optical waveguide are investigated. Then, based on this research, a new approximation method and calculation for an idea of expanding the near-infrared region are proposed.